PRESENT STATUS OF THE HIMALAYAN MAHSEER TOR PUTITORA, AN ENDANGERED SPECIES IN NAINITAL LAKES OF UTTAR PRADESH - PANDEY, K. D. (Journal of Indian Fisheries Association, 2006)
The present status of the. Himalayan m.ahseer in the three lab:es of Nainital district of U.P. is discussed based on the catch data from 1983- 84 to 1992-93. Yield of mahseer have shown a gradual decline in the recent years. Besides catch statistics, marlret arrivals and availability of fish to anglers have also shown a marked decline. Tor putitora is being considered as an endangered fish. It is therefore necessary to repopulate the lake9 with the mahseer by adopting better Inanagement practices like stocking the lakes continually with sufficient mahseer fingerlings and enforce stdct conservation measures to stop killing of juveniles.